2013
DOI: 10.1186/1756-3305-6-219
|View full text |Cite
|
Sign up to set email alerts
|

Armigeres subalbatus incriminated as a vector of zoonotic Brugia pahangi filariasis in suburban Kuala Lumpur, Peninsular Malaysia

Abstract: BackgroundIn 2011, we reported occurrence of natural human infections with Brugia pahangi, a filarial worm of dogs and cats, in a surburb of Kuala Lumpur, the capital city of Malaysia. Our preliminary entomological survey at that time suggested the mosquito species Armigeres subalbatus as the vector of the zoonotic infections. In this present report, we provide biological evidence to confirm our preliminary finding.FindingsA total of 1798 adult female Ar. subalbatus mosquitoes was caught in the vicinity of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 8 publications
0
32
0
4
Order By: Relevance
“…subalbatus, a species found widely in China, Japan, and Southeast Asia (Chaves et al 2015). The females feed primarily on people and are the natural vectors of filarial worms (Muslim et al 2013). Our findings that R. felis occurs widely in China in an increasing number of mosquito species that are known to feed on people should alert health workers to the possibility of mosquito-transmitted infections in their patients.…”
Section: Discussionmentioning
confidence: 74%
“…subalbatus, a species found widely in China, Japan, and Southeast Asia (Chaves et al 2015). The females feed primarily on people and are the natural vectors of filarial worms (Muslim et al 2013). Our findings that R. felis occurs widely in China in an increasing number of mosquito species that are known to feed on people should alert health workers to the possibility of mosquito-transmitted infections in their patients.…”
Section: Discussionmentioning
confidence: 74%
“…This is similar to a study conducted in Nigeria, which showed the infection rate of 10.1% and C. quinquefasciatus as the major vector (56.0%) (Manyi et al, 2014). In another study in Malaysia found 62 mosquitoes were positive and 27 mosquitoes infected with L3 out of 1,599 mosquitoes dissected for the presence of filarial larvae (Muslim et al, 2013).…”
Section: Resultsmentioning
confidence: 96%
“…It is mainly transmitted by the mosquito of the genera Mansonia and Anopheles , for example, Mansonia uniformis and Anopheles barbirostris , which are present in Singapore [ 54 , 55 ]. Regarding the felid parasite B. pahangi , it has recently been reported as a zoonotic pathogen inducing LF with domestic cats as reservoir [ 13 , 58 ] in several transmission events in the suburb of the capital city of Malaysia, Kuala Lumpur [ 13 , 58 ], and in a semirural town of Selangor [ 12 , 59 ]. The incriminated vector was Armigeres subalbatus [ 12 , 59 ], a mosquito species also present in Singapore [ 55 , 60 ].…”
Section: Discussionmentioning
confidence: 99%